Viabilidade da medida da velocidade de propagação sonora em tecidos oculares in vivo e sua correlação com a elasticidade presumida - Ribeiro, Joao Crispim Moraes Lima [UNIFESP] (2016)
Introduction: To date, it has never been demonstrated the propagation speed of sound in human corneas and lens in vivo. With the advent of Optical Coherence Tomography (OCT), it became possible to determine the dimensions of the ocular tissues without the interference of sound propagation speed and to use this information to define the real propagation speed of sound for each patient and individualized structure. Purpose: To determine the speed of sound in the cornea and lens from groups of patients that theoretically exhibits differences in tissue elasticity and to correlate the determined velocity in each group with the expected tissue elasticity of the cornea and lens. Methods: We studied 100 eyes from 50 patients: 50 young (less than 40 yearsold) with keratoconus and no cataract (Group 1) and 50 elderly (more than 50 years-old) with cataracts and no corneal changes (Group 2). All patients had their corneas and lenses thicknesses measured by ultrasonographic methods: UBM - Ultrasound Biomicroscopy, Vumax II®, and UP - Ultrasonic Pachymetry, Pachette 2 model DGH 550®, as well as by optic methods: OCT (RTVue®, Lenstar® and Visante®). Corneal central thickness was evaluated by UBM, USP, RTVue®, Visante®, and Lenstar®. Axial thickness of the lens was evaluated by UBM and Lenstar®. Based on standard ultrasonic speed used in UP (1640 m/s) and UBM (1548 m/s), we calculated the real sound propagation speed in each tissue. Results: Based on UP, the mean corneal speed of sound on Group 2 (1611 m/s) was faster than on Group 1 (1571 m/s) (P < 0.05). Based on UBM, the mean lens speed of sound on Group 2 (1662 m/s) was faster than on Group 1 (1602 m/s) (P < 0.0001). Discussion: It is known that sound propagates faster in materials with lower elasticity. We found that the speed of sound on keratoconic corneas (high elasticity) was slower and on cataract lens (lower elasticity) was faster than normal corneas and lens in vivo.